Families in America - Brown, Susan L., 1971- (Sociology in the 21st century (University of California Press), 2017)
"Charting the diverse pathways of family life, this book addresses how family formation and dissolution unfold over the life course with an emphasis on how these trends differ across subgroups. Reflecting larger societal patterns of economic inequality, family pathways are structured differently for the most and least advantaged. The book documents current trends in singlehood, cohabitation, marriage, and childbearing as well as widowhood, divorce, and remarriage. It also provides a critical lens for interpreting why family change occurs and its significance for the well-being of children and adults. Today's family experiences are contexualized in a larger sociohistorical context to show that family change is persistent across historical time. The challenges families face inform policy debates on topics such as welfare reform, work-life balance, and population aging. The book concludes with an assessment of how the demography of families is likely to shape the familial experiences of future generations"--Provided by publisher